2019
DOI: 10.18393/ejss.510744
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land use types on selected soil physical and chemical properties: The case of Kuyu District, Ethiopia

Abstract: Information about effects of land use types on selected soil physical and chemical properties is essential in sustainable utilization of soil resources. Therefore, this study was conducted to evaluate effects of land use types on selected soil physical and chemical properties on Kuyu district, Ethiopia. Totally, 24 composite soil samples were collected from grass, cultivated, forest and grazing lands by two soil depths (0-20 cm and 20-40 cm) with three replications. The two way analysis of variance was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 22 publications
18
32
0
1
Order By: Relevance
“…This finding clearly showed the positive impact of SLM practices on soil displacement and deposition processes. Our finding agrees with those of Ademe et al (2017), and Tufa et al (2019). Ademe et al (2017) found higher sand and silt contents, but lower clay content in the untreated watershed than the treated watershed.…”
Section: Particle Size Distributionsupporting
confidence: 93%
See 4 more Smart Citations
“…This finding clearly showed the positive impact of SLM practices on soil displacement and deposition processes. Our finding agrees with those of Ademe et al (2017), and Tufa et al (2019). Ademe et al (2017) found higher sand and silt contents, but lower clay content in the untreated watershed than the treated watershed.…”
Section: Particle Size Distributionsupporting
confidence: 93%
“…Ademe et al (2017) found higher sand and silt contents, but lower clay content in the untreated watershed than the treated watershed. Moreover, Tufa et al (2019) found no significant difference in sand particle proportions under land-use types, soil depths, and in the interaction of land-use types with soil depth. Both studies found significant differences in silt and clay proportions at different land-use types, with higher sand content on the surface and higher clay content at the subsurface of the soils.…”
Section: Particle Size Distributionmentioning
confidence: 68%
See 3 more Smart Citations